Joint effect of tobacco, alcohol, and oral HPV infection on head and neck cancer risk in the French West Indies - Aviane Auguste; Jacqueline Deloumeaux; Clarisse Joachim; Stanie Gaete; Leah Michineau; Cécile Herrmann‐Storck; Suzy Duflo; Danièle Luce (Cancer Medicine, 2020)
Abstract We investigated the role of tobacco and alcohol consumption on the occurrence of head and neck squamous cell carcinomas (HNSCC), and the joint effects of these factors with oral human papillomavirus (HPV) infection in the French West Indies, in the Caribbean. We conducted a population‐based case‐control study (145 cases and 405 controls). We used logistic regression models to estimate adjusted odds ratios (OR) and their 95% confidence intervals (CI). Two‐way interactions were assessed on both multiplicative and additive scales. Current smoking (OR = 11.6, 95% CI = 6.7‐20.1), drinking more than five glasses of alcohol per day (OR = 2.7, 95% CI = 1.2‐4.7), and oral infection with High‐risk HPV (OR = 2.4, 95% CI = 1.1‐5.0) were significantly associated with HNSCC. The combined exposure to tobacco and alcohol produced a significant synergistic effect on the incidence of HNSCC. Oral infection with High‐risk HPV increased the risk of HNSCC in never smokers and nondrinkers. The effects of tobacco, alcohol, and of the combined exposure of tobacco and alcohol were substantially lower in HPV‐positive than in HPV‐negative HNSCC. This is the first case‐control study to investigate the role of tobacco smoking, alcohol drinking and oral HPV infection in an Afro‐Caribbean population. Although each of these risk factors has a significant effect, our findings indicate that tobacco and alcohol play a less important role in Hr‐HPV‐positive HNSCC. Further investigations are warranted notably on the interaction of these three risk factors by cancer site.